2015
DOI: 10.1371/journal.pone.0130346
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Lipids Are Associated with Alcoholic Liver Cirrhosis and Represent Potential Biomarkers for Risk Assessment

Abstract: Liver disease is the greatest cause of death related to alcohol and a major public health problem. While excessive alcohol intake results in hepatosteatosis in most individuals, this can progress in some to more severe forms of liver disease including fibrosis and cirrhosis. An ongoing challenge in the management of alcoholic liver disease is the identification of liver injury early in the disease process such that intervention strategies can prevent serious long term outcomes. Given that excessive alcohol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 27 publications
(29 reference statements)
2
25
1
Order By: Relevance
“…Liver steatosis is a basic hallmark in alcoholic liver disease, and alcohol-induced metabolic alterations lead to increased fatty acid synthesis and decrease fat metabolism [ 22 ]. Circulating lipids are also associated with ALD and proposed as biomarkers in risk assessment [ 23 ]. We have demonstrated increased fat deposition in chronic plus ethanol-fed mice liver by Nile red staining and triglyceride content.…”
Section: Discussionmentioning
confidence: 99%
“…Liver steatosis is a basic hallmark in alcoholic liver disease, and alcohol-induced metabolic alterations lead to increased fatty acid synthesis and decrease fat metabolism [ 22 ]. Circulating lipids are also associated with ALD and proposed as biomarkers in risk assessment [ 23 ]. We have demonstrated increased fat deposition in chronic plus ethanol-fed mice liver by Nile red staining and triglyceride content.…”
Section: Discussionmentioning
confidence: 99%
“…this has proven to be very difficult because the correlations between blood and liver lipid species drastically decrease after the transition from NAFL to NASH (5). We previously used lipidomics to compare serum lipid profiles from excessive chronic drinkers without liver disease to those with advanced alcoholic cirrhosis, and showed that circulating lipids associate with alcoholic liver cirrhosis and represent potential biomarkers for risk assessment (6). The aim of the current study was to gain a more comprehensive understanding of the hepatic and plasma lipidomic changes in morbidly obese subjects with NAFL or NASH compared with morbidly obese subjects without NAFLD, and to gain insight into lipid species that are linked to disease progression through the different stages of NAFLD.…”
mentioning
confidence: 99%
“…However, a negative correlation with HbA1c indicates an at least partly preserved effect of adiponectin on glucose homeostasis. Since we found no association with indices of insulin sensitivity and beta-cell function, this effect is most likely attributable to the specific effect of adiponectin on the hepatic glucose production via identified regulatory pathways for glucose and lipid metabolism at transcriptional levels [51,52].…”
Section: Discussionmentioning
confidence: 65%